DESTRUCTION OF GRAPHITIZED STEELS AT CYCLIC LOAD - I. P. Volchok; I. V. Akimov; A. A. Mitjaev; I. M. Andrejko; N. A. Svidunovich; S. E. Belskij; D. V. Kuis; A. P. Melnikov; M. A. Sadoha (Литьë и металлургия)
It is determined that graphitized steels are perspective construction material, the breakage resistance and mechanical characteristics of which are determined to a considerable degree by form of graphitic impurities.